Prevalence and diversity of ectoparasites in scavenging chickens (Gallus domesticus) and their association to body weight - edy riwidiharso; darsono darsono; endang ariyani setyowati; hery pratiknyo; EMING SUDIANA; SLAMET SANTOSO; EDY YANI; imam widhiono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Riwidiharso E, Darsono, Setyowati EA, Pratiknyo H, Sudiana E, Santoso S, Yani E, Widhiono I. 2020. Prevalence and diversity of ectoparasites in scavenging chickens (Gallus domesticus) and their association to body weight. Biodiversitas 21: 3163-3169. Domestic chickens (Gallus domesticus) which are traditionally fed by scavenging on farms predispose them to ectoparasites infestation. In this study, a preliminary survey was conducted on the common ectoparasites on G. domesticus in the rural areas of Banyumas. The purposes of this study were to determine the diversity of ectoparasites, their prevalence, and their relationship to the chickens body weight. This research was conducted by the survey method from December 2019 to April 2020 in five villages around the city of Purwokerto, Banyumas District, Central Java, Indonesia viz., Kedungwuluh, Kedungwringin, Kutasari, Karangsalam, and Karanggintung. Data analysis was conducted by Shannon Wiener and Evenness indexes. Analysis of variance was used to calculate the difference in prevalence among sample locations. Regression correlation analysis was used to determine the relationship between prevalence and chicken body weight. The results showed that there were six ectoparasite species  i.e., Menopon gallinae, Menacanthus cornutus, Lipeurus caponis, Dermanysus gallinae, Megninia ginglymura, and Haemaphysallis sp. parasitizing G. domesticus. The number of ectoparasite individuals among locations was significantly different (F 5.59 < 32.45; p <0.05). The most number of ectoparasite was found in Karangsalam (272 individuals). The most prevalent ectoparasite was M. cornutus (45%), followed by L. caponis (40%), and the lowest was M. synglineura (25%). Ectoparasite prevalence was associated with chicken weight loss (r = 0.98). The prevalence of ectoparasite of domestic chickens farm in the Banyumas Regency is classified as low but has the potential to influence body weight.